2015
DOI: 10.1530/eje-15-0395
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with primary hypothyroidism related to BMI

Abstract: Objective: Many patients treated for primary hypothyroidism have an unexplained reduced quality of life (QOL). We studied the relation between QOL and various parameters in treated hypothyroid patients. Design and methods: QOL analysis was done in 90 consecutive patients (77.8% females) treated for primary hypothyroidism. QOL was measured by the questionnaires Short-Form 36, Hospital Anxiety and Depression Scale and MFI20. Post hoc analysis was performed on the relation of QOL at baseline and BMI, thyroid horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 42 publications
3
45
1
3
Order By: Relevance
“…A recent previous study showed that females in the lowest-normal TSH tertile had a higher risk of depressive symptoms evaluated with Beck Depression Inventory even among patients with normal TSH levels in general population [21]. In contrast, another recent paper reported that parameters of SF-36 were not dependent on serum TSH and fT4 levels in hypothyroid patients on levothyroxine treatment [22]. The reason of this controversy may come from that personal and environmental factors can affect the answers of the individuals participating in the survey.…”
Section: Disclosurementioning
confidence: 93%
“…A recent previous study showed that females in the lowest-normal TSH tertile had a higher risk of depressive symptoms evaluated with Beck Depression Inventory even among patients with normal TSH levels in general population [21]. In contrast, another recent paper reported that parameters of SF-36 were not dependent on serum TSH and fT4 levels in hypothyroid patients on levothyroxine treatment [22]. The reason of this controversy may come from that personal and environmental factors can affect the answers of the individuals participating in the survey.…”
Section: Disclosurementioning
confidence: 93%
“…1 Despite adequate restoration of biochemical euthyroidism with replacement therapy with levothyroxine (LT4), a substantial part of patients (~10-15%) display significant impairment of psychological well-being compared to controls of similar age and sex and show decrements in health status. [2][3][4][5][6] There are a couple of explanations for these persisting symptoms. First, the presence of associated autoimmune diseases or thyroid autoimmunity per se could account for persisting symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The overweight is probably a nota taken feature in patients with hypothyroidism, and might be a great contributor to the decrease of the quality of life". Once again an AoC condition, now in people with hypothyroidism, impacts in the quality of life and with that in the feeling of being healthy [4].…”
Section: Discussionmentioning
confidence: 99%